Comparison of the efficacies of abatacept and tocilizumab in patients with rheumatoid arthritis by propensity score matching. Issue 7 (5th August 2015) - Kubo, Satoshi; Nakayamada, Shingo; Nakano, Kazuhisa; Hirata, Shintaro; Fukuyo, Shunsuke; Miyagawa, Ippei; Hanami, Kentaro; Saito, Kazuyoshi; Tanaka, Yoshiya
Abstract : Objective: To compare the clinical outcomes at 1 year after the treatment with either abatacept or tocilizumab in patients with rheumatoid arthritis in routine clinical practice. Methods: To overcome potential bias in allocation to treatment with abatacept or tocilizumab, a propensity score based on multiple baseline characteristics variables was calculated and 102 of 194 patients treated with abatacept and 102 of 273 patients treated with tocilizumab were statistically extracted. Clinical outcomes were assessed. Results: The baseline characteristics were statistically comparable. At week 52, 72%/69% of patients (abatacept/tocilizumab) were still receiving treatment. The Simplified Disease Activity Index (SDAI) decreased from 28.7/27.7 at baseline to 14.0/12.5 at week 52 with abatacept/tocilizumab, respectively. At week 52, the remission rates for abatacept/tocilizumab were 18%/20%, respectively. No statistical difference in clinical efficacy between abatacept and tocilizumab was seen. Moreover, a subanalysis showed that abatacept and tocilizumab had similar effectiveness with or without methotrexate. However, prognostic factors at baseline contributing to the Clinical Disease Activity Index at week 52 were different between the two groups by multiple regression analysis. A higher rheumatoid factor (RF) titre and lower SDAI at baseline were associated with lower SDAI at week 52 in patients treated with abatacept, whereas patients receiving tocilizumab with a lower Health Assessment Questionnaire Disability Index and who were biologics-naïve at baseline had a lower SDAI at week 52. Conclusions: We compared patients treated with abatacept or tocilizumab after statistical adjustment by propensity score matching. Clinical efficacies, including SDAI, were comparable in both treatment groups. However, the predictive factors were different: abatacept appears to benefit patients with higher RF titres, and early induction of tocilizumab is an important factor for good clinical efficacy.